Peran Dinas Pekerjaan Umum Dan Penataan Ruang Dalam Pengendalian Banjir Di Kota Surakarta - Kuspiyanti Wulandari (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2022)
Flood control is one of the tasks, principals, and functions of the Surakarta City Public Works and Spatial Planning Office in achieving the goal of freeing the city of Surakarta from flooding. The problems that exist in flood control are that there are still many flood points found in the city of Surakarta, there are still complaints submitted about the damage to flood control facilities submitted by the community. The purpose of this study is to describe the role of the Department of Public Works and Spatial Planning in Flood Control in Surakarta City by using the theory according to Mudrajad Kuncoro (2014: 113 – 114) which consists of 3 indicators, namely coordinator, facilitator, and stimulator. The method used in this study is to use a qualitative method with a descriptive approach. Data collection techniques used are observation, interviews, and documentation. Informants in this study consisted of the Head of Water Resources, Head of Operation and Maintenance Section, Staff of Water Resources, and Volunteers. The data analysis technique in this research is an interactive data analysis model. The result of this research is that the Department of Public Works and Spatial Planning in flood control in Surakarta acts as a coordinator, facilitator and stimulator. However, there are still obstacles to achieving the goal of flood control, namely the lack of quick action or handling of complaints and less optimal in conveying information on improving facilities and the use of complaint media, and lack of socialization to the public regarding regulations, permits, and fees for closing the channel over the river and drainage. so that many people still close the channel without permission.